Filogenetik Ikan Ekstremofil Edible Populasi Magelang Menggunakan Gen Cytochrome Oxydase I - Jefri Permadi; Ana Rochvita; Rr. Citra Permata Kusuma Anggraini; Flandrianto Sih Palimirmo (Journal of Research and Technology, 2022)
The Cethol fish was used as a dietary raw material of chips fish by local people in Magelang. The population of the fish was decreased and impacted to fish chips production. The Cethol fish farming could be the one of solution to maintain the stock of this fish as dietary raw material. Nevertheless, the taxonomic status of Cethol fish as the primary information of in Magelang still unclear. Taxonomic status is of organisms is useful to inform biology, reproduction and traits of candidate species will be farmed. The aim of research is revealing the taxonomic status of Cethol fish in Magelang using common barcoding marker Cytochrome Oxidase I (COI) from mitochondrial DNA. The COI gene sequences of Cethol fish from Magelang and other sequence samples from NCBI were used to construct the phylogenetic tree and haplotype network approach to reveal the similarity and clustered of the fish sequence samples. The maximum likelihood and minimum evolution were considered as construction tree method by Kimura 2 parameter statistic model and 1000 bootstrap value. The Median joining statistic model was generated to reveal grouping form and substitution rate of each samples. The phylogenetic tree was constructed from COI gene of Cethol fishes from Magelang are grouped in the same clade and monophyletic with the Poecilia reticulata COI gene from South America as the origin of the fish species. Meanwhile, the P.reticulata from Bengkulu, Sumatera and Java were clearly separated with the samples from Magelang but still in haplogroup with the South America sequence samples. Those result are strengthen the previously notion that the Cethol fish in Magelang is a group species of P.reticulata from South America.